Motricidad fina y niveles de la escritura en niños de la Institución Educativa Inicial UNAP María Reiche, San Juan Bautista 2024 - Davila Ahuanari, Katty Tatiana (2024)
The main objective of this study is to analyze the relationship between fine motor skills development and writing levels in the children of the Early Education Institution UNAP María Reiche San Juan during the year 2024. The approach adopted is quantitative, with a correlational and cross-sectional design. The sample includes all students of the institution, totaling 102 participants. For data collection, the observation technique was used through a guide specifically designed for this purpose, whose validity was endorsed by a team of subject matter experts. The results revealed a Spearman's Rho correlation coefficient of r = 0.704, with a significance level of 0.05, indicating a positive and significant correlation between fine motor skills development and writing levels. In conclusion, the main hypothesis is confirmed, showing a significant relationship between both variables, where children with better fine motor skills development tend to have more advanced writing abilities.